1991
DOI: 10.1159/000200686
|View full text |Cite
|
Sign up to set email alerts
|

Single Morning and Nightly Doses of Ranitidine 300 mg: An Appraisal of Their Antisecretory Effects by Continuous pH Monitoring

Abstract: Gastric acidity of 12 patients with healed duodenal ulcers was continuously monitored over 24 h in order to assess the antisecretory effects of two different administration times of a single daily dose of ranitidine 300 mg. Each patient orally received either (a) placebo at 08.00 h and 22.00 h; (b) ranitidine 300 mg at 08.00 h and placebo at 22.00 h, or (c) placebo at 08.00 h and ranitidine 300 mg at 22.00 h in randomized and double-blind fashion. Each medication was administered on three separate occasions, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Ranitine, given during night-time, was associated with a higher inhibition of intragastric acidity either in healthy subjects [80], and in patients with duodenal ulcer with nocturnal acid breakthrough [81].…”
Section: H 2 -Receptor Antagonistsmentioning
confidence: 94%
“…Ranitine, given during night-time, was associated with a higher inhibition of intragastric acidity either in healthy subjects [80], and in patients with duodenal ulcer with nocturnal acid breakthrough [81].…”
Section: H 2 -Receptor Antagonistsmentioning
confidence: 94%
“…Following this, a single daily night regimen of H 2 -receptor antagonists was shown to produce better control of gastric pH compared to once-a-day morning administration. 92,93 This is because the intragastric contents are buffered by food during the day, leading to lower apparent antisecretory effect following morning drug administration.…”
Section: Circadian Dependencymentioning
confidence: 99%
“…Recent clinical studies have shown that large, single, morning doses of H2-antagonists are as effective as equivalent single nocturnal doses in promoting healing of DUs (22,23), although morning administration has a shorterlasting action than bedtime dosing (22, 24). This apparent discrepancy may be explained by the fact than inhibition of diurnal acidity may be more important than the inhibition of nocturnal acidity, provided that the period of reduced acidity obtained is long enough to allow the healing process to take place.…”
Section: Morning Administration Of Nizatidinementioning
confidence: 99%